2022
DOI: 10.25034/ijcua.2022.v6n2-7
|View full text |Cite
|
Sign up to set email alerts
|

Informal Use of “Marginal Open Space” Along Residential Streets in a Nigerian City

Abstract: In today’s highly regulated cities, a conspicuous pattern of marginal open space has emerged between buildings and streets. With rapid population growth, different activities are also emerging in the open spaces, particularly in the cities of developing countries. This study explores the informal use of the marginal open spaces along residential streets in Ile-Ife, Nigeria, to identify the physical planning implications. The data for this study were mainly collected through a questionnaire survey and open spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Openness was one of the important physical features affecting the comfort of street space. The sky element could improve human perception and psychology (Adebara et al 2022, Xu et al 2023. In the street space, the high openness can increase the aesthetic of the streetscape, thereby promoting the attractiveness and comfort of the street built environment (Ma et al 2021).…”
Section: The Influence Of Street Built Environment On Human Positive ...mentioning
confidence: 99%
“…Openness was one of the important physical features affecting the comfort of street space. The sky element could improve human perception and psychology (Adebara et al 2022, Xu et al 2023. In the street space, the high openness can increase the aesthetic of the streetscape, thereby promoting the attractiveness and comfort of the street built environment (Ma et al 2021).…”
Section: The Influence Of Street Built Environment On Human Positive ...mentioning
confidence: 99%
“…The results of this study corroborate the findings of previous research that the need for economic survival and the lack of environmental amenities are important reasons why people in developing countries keep using public spaces for different activities despite strict regulations by urban planners (Abolade & Adeboyejo, 2013;Adedeji et al, 2014;Afon et al, 2006). Due to the limited economic means available to the poor and the government's disregard for the deficiency of natural amenities, urban public spaces have become workplaces for the underprivileged (Adebara et al, 2022;Handoyo & Setiawan, 2018;Okanlawon & Odunjo, 2016). The study also showed that culture and social lifestyle were the third important factor determining everyday urbanism and the use of the streets.…”
Section: Factors Influencing Everyday Urbanism and Use Of Streetsmentioning
confidence: 99%
“…Although strict regulations and control over public spaces exist, people-centred (bottom-up) interventions occur in traditional city centres. For instance, some residents often appropriate the street space for various purposes, such as informal trading, prayers, and social ceremonies (Adebara, 2017;Adebara et al, 2022). However, while such action exemplifies the rights people claim to suit their requirements and improve their daily living experience, some argue that the misuse of public spaces can generate land-use problems (Adedeji et al, 2014;Jelili & Adedibu, 2006).…”
Section: 10 Introductionmentioning
confidence: 99%